ANALISIS KEBIJAKAN GERAKAN TUJUH KEBIASAAN ANAK INDONESIA HEBAT (7KAIH) - TIYAS, AFRISKA HERNANING; Mufarrihul Hazin; Haris Supratno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The cultivation of student character from an early age is a primary priority in Indonesia's basic education system. One of the key character education policies is the implementation of the Seven Habits of Great Indonesian Children (7H-GIC), initiated by the Ministry of Primary and Secondary Education. This study aims to analyze the 7H-GIC program policy conceptually, examine its policy structure, explore its implementation strategies, and identify the challenges and obstacles in its application through a literature review. The research method used is library research, which involves analyzing and reviewing various written sources relevant to the topic of the Seven Habits program. Data were analyzed using a qualitative descriptive method, which involves describing and explaining findings in narrative form. The study reveals that the strategy applied is based on the 1% rule—making small daily improvements consistently over time to generate significant long-term change. Furthermore, an enjoyable approach, modeling through example, and consistency are key to shaping a golden generation.